Perancangan Board Game Kolaboratif. Studi Kasus: Legenda Gunung Tondoyan - Nadia Mahatmi (Universitas Multimedia Nusantara, 2021)
Collaboration is one of the soft skills needed in the 21st century. One way to advance collaborative skills is to use a board game. It is common today to find board games for learning purposes. The design of this collaborative board game uses qualitative methods, namely literature studies, brainstorming, physical prototypes, software prototypes, and design documentation. With this research, it is hoped that it will help understand how to design a collaborative board game. Keywords: board game; collaborative; prototype